2019
DOI: 10.3390/ijms20102597
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of Nanobodies Recognizing the Human Chemokine Receptor CCR7

Abstract: The chemokine receptor CCR7 plays a pivotal role in health and disease. In particular, CCR7 controls homing of antigen-bearing dendritic cells and T cells to lymph nodes, where adaptive immune responses are initiated. However, CCR7 also guides T cells to inflamed synovium and thereby contributes to rheumatoid arthritis and promotes cancer cell migration and metastasis formation. Nanobodies have recently emerged as versatile tools to study G-protein-coupled receptor functions and are being tested in diagnostics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…135 A recent study reported engineered nanobodies that target CCR7 which can be used for therapeutic and diagnostic purposes. 136 Another study indicated that both prophylactic and therapeutic treatments of CIA-humanized CCR7 mice with anti-human CCR7 monoclonal antibody led to complete resistance to CIA and arrested progression, thus highlighting that CCR7 could be a potential therapeutic target in RA. 136 One potential therapeutic target in RA is CX 3 CL1 which has been blocked in a clinical trial using a monoclonal antibody as a treatment for RA.…”
Section: Effect Of Chemokines In Ra Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…135 A recent study reported engineered nanobodies that target CCR7 which can be used for therapeutic and diagnostic purposes. 136 Another study indicated that both prophylactic and therapeutic treatments of CIA-humanized CCR7 mice with anti-human CCR7 monoclonal antibody led to complete resistance to CIA and arrested progression, thus highlighting that CCR7 could be a potential therapeutic target in RA. 136 One potential therapeutic target in RA is CX 3 CL1 which has been blocked in a clinical trial using a monoclonal antibody as a treatment for RA.…”
Section: Effect Of Chemokines In Ra Therapymentioning
confidence: 99%
“…136 Another study indicated that both prophylactic and therapeutic treatments of CIA-humanized CCR7 mice with anti-human CCR7 monoclonal antibody led to complete resistance to CIA and arrested progression, thus highlighting that CCR7 could be a potential therapeutic target in RA. 136 One potential therapeutic target in RA is CX 3 CL1 which has been blocked in a clinical trial using a monoclonal antibody as a treatment for RA. 137 The humanized anti-CX 3 CL1 monoclonal antibody E6011 was found to be safe, well tolerated, and exhibited efficacy for 52 weeks in active RA patients who were non-responders or intolerant to MTX or TNF inhibitor therapies.…”
Section: Effect Of Chemokines In Ra Therapymentioning
confidence: 99%
“…Nanobodies blocking protumor chemokines [CXCL10 ( 147 )] or fused to anti-tumor chemokines [CCL21 ( 148 )] have demonstrated functionality in microfluidic devices, but have yet to be tested in vivo . Antagonistic nanobodies for chemokine receptors such as ChemR23 ( 149 ), US28 ( 150 ), CCR7 ( 151 ), CXCR4 ( 152 154 ), and CXCR7 ( 154 , 155 ) have also been developed. Smolarek et al ( 156 ) developed the first nanobody inhibiting the Duffy antigen receptor for chemokines (DARC), but it has yet to be applied in tumor models.…”
Section: Nanobodies: Synergy With Other Cancer Therapeuticsmentioning
confidence: 99%
“…It interacts with CCR7 through bimolecular uorescence complementary recognition without interfering with G protein coupling and downstream signaling. Targeted analysis of the migration and invasion process of CCR7 [74]. Chemokine C-X-C motif chemokine ligand 5 (CXCL5) has functions such as chemotaxis of neutrophils, proangiogenesis, and involvement in in ammatory responses.…”
Section: Analysis Of Hub Genes That Play a Diagnostic And Therapeutic Role In Ramentioning
confidence: 99%